Sustainable Employment and Economic Growth - Kamal, Madiha; Rauf, Muhammad Bilal Bin Abdul; Fatima, Ambreen (Pakistan Journal of Humanities and Social Sciences, 2023)
This study investigates the relationship between economic growth and employment in Pakistan at the aggregate and sectoral levels. It uses different econometric models, such as the Cobb-Douglas production function, the employment demand model, and the ARDL model, to analyze the data and test the hypotheses. It finds that economic growth does not create enough jobs for the population and that there is a mismatch between the output and employment growth of different sectors. It shows that the service sector, which is the fastest-growing sector in Pakistan, has a contradictory and weak impact on employment and growth, and that it relies on more capital-intensive technology. It recommends that the government and policy makers should focus on the real sector, especially the industry sector, which has a positive and significant effect on employment and growth. It also suggests that Pakistan should use its large population as a source of labor-intensive development rather than relying on technology.